Phase 2 trial of concurrent bevacizumab and transhepatic arterial chemoembolization in patients with unresectable hepatocellular carcinoma. Issue 5 (6th November 2012) - Buijs, Manon; Reyes, Diane K.; Pawlik, Timothy M.; Blackford, Amanda L.; Salem, Riad; Messersmith, Wells A.; Weekes, Colin D.; Mulcahy, Mary; Kamel, Ihab R.; Geschwind, Jean‐Francois H.
Abstract BACKGROUND: Vascular endothelial growth factor is up‐regulated in hepatocellular carcinoma (HCC) and is further up‐regulated after transhepatic arterial chemoembolization. The authors of this report conducted a phase 2 trial to evaluate the safety and efficacy of bevacizumab combined with chemoembolization in patients with unresectable HCC. METHODS: Patients who had an Eastern Cooperative Oncology Group performance of status 0 to 2, a Child‐Pugh score of A or B, and Barcelona Clinic Liver Cancer stage B or C HCC were eligible. Treatment consisted of bevacizumab every 2 weeks and chemoembolization during the third week of a 6‐week cycle for up to 3 cycles over 6 months. The primary endpoints were safety and efficacy. RESULTS: Twenty‐five patients received chemoembolization and bevacizumab. The most common grade 3 and 4 events after the first treatment cycle were leukocytopenia (12%), fatigue (12%), and hyponatremia (12%). Serious toxicities that had a known association with bevacizumab were observed in 4 patients. Thirty‐day mortality was 0%. The median time to tumor progression for the targeted lesions was not reached, and overall survival was 10.8 months. The objective response rate was 60% using enhancement response evaluation criteria, and the disease control rate was 100%. CONCLUSIONS: Concurrent treatment with bevacizumab and chemoembolization was safe in carefully selected patients and demonstrated antitumor activity in patients with unresectable HCC. These results support the further development of bevacizumab combined with chemoembolization as a treatment for unresectable HCC. Cancer 2013. © 2012 American Cancer Society.